Promotion of physical activity among children through a community intervention : the case of the ciclovía of Bogotá (2016)
Background and Objectives: Only one in four children and youth, between 6 and 15 years, meet International recommendations on physical activity (PA). The Ciclovia is a promising community-based Intervention implemented in at least 24 countries to promote PA and to reduce sedentary behaviors (SB). Nonetheless, most of the studies have been conducted among adults and no studies have assessed PA and SB among children. The aim of this study is to assess the associations between levels of PA and SB among children who participate in the Bogotá's Ciclovia compared to those who do not participate. Methods: The study sample included 769 children aged 9-11 years. PA and SB were measured using a standardized protocol of accelerometry and Ciclovia's participation was self-reported. Analysis include multilevel generalized mixed models and generalized additive model (GAM). Results: The prevalence of participating weekly and at least once a month m the Ciclovia was 5.46% and 31.21% respectively